2017
DOI: 10.1126/science.aan5830
|View full text |Cite|
|
Sign up to set email alerts
|

Biological fabrication of cellulose fibers with tailored properties

Abstract: Cotton is a promising basis for wearable smart textiles. Current approaches that rely on fiber coatings suffer from function loss during wear. We present an approach that allows biological incorporation of exogenous molecules into cotton fibers to tailor the material's functionality. In vitro model cultures of upland cotton () are incubated with 6-carboxyfluorescein-glucose and dysprosium-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid-glucose, where the glucose moiety acts as a carrier capable of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 33 publications
(34 reference statements)
3
39
0
Order By: Relevance
“…The analysis showed identified selection signatures at 670 and 232 PSGs in the G. australe and G. arboretum genomes, respectively (Figure S6, Data S1). Subsequent KEGG pathway analysis indicated that statistically significant ( P < 0.05) enrichment among the G. australe PSGs for the ‘Other types of O‐glycan biosynthesis’ (ko00514) pathway (Figure S7), which was associated with cotton fibre strength in studies of in G. arboreum (Hernandez‐Gomez et al ., ; Natalio et al ., ). There was also significant enrichment among the G. australe PSGs for ‘Riboflavin metabolism’ (ko00740) (Asai et al ., ; Boubakri et al ., ; Deng et al ., ) and GPI (Shen et al ., ) (Figure S7), pathways which have been implicated in plant responses to biotic stresses.…”
Section: Resultsmentioning
confidence: 97%
“…The analysis showed identified selection signatures at 670 and 232 PSGs in the G. australe and G. arboretum genomes, respectively (Figure S6, Data S1). Subsequent KEGG pathway analysis indicated that statistically significant ( P < 0.05) enrichment among the G. australe PSGs for the ‘Other types of O‐glycan biosynthesis’ (ko00514) pathway (Figure S7), which was associated with cotton fibre strength in studies of in G. arboreum (Hernandez‐Gomez et al ., ; Natalio et al ., ). There was also significant enrichment among the G. australe PSGs for ‘Riboflavin metabolism’ (ko00740) (Asai et al ., ; Boubakri et al ., ; Deng et al ., ) and GPI (Shen et al ., ) (Figure S7), pathways which have been implicated in plant responses to biotic stresses.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, most chemical modification approaches are carried out on the commercial papers, resulting in the poor uniformity of structure due to artificial operation [29]. To improve the poor uniformity of structure, new paper modification approaches based on the papermaking process, such as addition of chemical reagents during the pulping process [142], can be used to produce special functional papers. Finally, hydrophobic patterning and barrier modification approaches will be further developed for integration with paperbased electronic chips [143].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Our very initial studies were aimed at studying the biological selectivity uptake of different classes of organic dyes by the intermembranar glucose/sucrose transporter(s) (GLUT) using an in vitro culture of cotton . For this purpose, the cotton flowers were collected on the second day postanthesis and sterilized; the ovules were then carefully removed and floated in a Beasley and Ting medium (in a Petri dish) .…”
Section: Methodological Approach To Tailoring Functionalities Of Cottmentioning
confidence: 99%
“…After exposing the fibers to UV light, the fibers became fluorescent. To ensure the coloration/fluorescence was biologically integrated and not merely a redeposition of the dye due to evaporation inside the Petri dish, we performed a small‐angle X‐ray scattering (SAXS), wide‐Angle X‐ray scattering (WAXS), and single fiber mechanical tensile analysis . The SAXS and WAXS showed an increased structural amorphization and the fiber mechanical tensile analysis revealed a decrease in the fiber's mechanical properties.…”
Section: Methodological Approach To Tailoring Functionalities Of Cottmentioning
confidence: 99%